Eating Disorders in Adolescent Girls. Gynecologist's Point of View - Elena V. Sibirskaya; Irina V. Karachentsova; Viktoriya V. Naumova; Mariya Yu. Chernysheva; Maksim A. Naumov; Akim V. Karelin; Daria V. Fadeeva; Ilia I. Bikhert (Union of pediatricians of Russia, 2024)
This review presents an analysis of the literature data for the last 10 years (2012-2022) investigating the effect of eating disorders on the health of adolescent girl, its diagnosis, and possible tactics of gynecologist. The most common predictor of restoring menstrual function in girls with this pathology is body mass index change, however normalization of weight does not lead to remission in all cases. Thus, estimation of fat percentage, insulin-like growth factor, and leptin is more effective. We suggest directing further research on the study of more effective methods of reproductive disorders correction and the development of multidisciplinary clinical guidelines for the effective diagnosis and management of eating disorders and any gynecological complications.